Design Analysis of Triangular Minipile for Cohesive Soil: A Study Case - Wardani, MK; Aulady, MFN; Syafiarti, AID; P, Febiana (Journal of Civil Engineering, Planning and Design, 2022)
Triangular minipile foundations are still rarely encountered in construction even though they are still being produced. The use of minipile foundations can be considered in the design of foundations with soft soil depth of 10 m. This study was conducted to design for a triangular minipile on soft soil by considering the bearing capacity of either the foundation or the material, settlement, as well as the implementation method and cost budget. The soil data used is NSPT data with a soft soil depth of up to 8 m with a 2-storey shophouse building load. The recommended results are given when using a minipile of 28x28x28 cm compared to 32x32x32 cm, the need for a minipile is different from 3 to 6 piles at a depth of 6 m with a load of 40.37 tons. A triangular minipile with dimensions of 28 x 28 x 28 cm has total settlement of 6.02 cm. A triangular minipile with dimensions of 32 x 32 x 32 cm has total settlement of 3.87 cm. The minipile foundation implementation method using the "press in pile" Driving is carried out using an HSPD machine with a capacity of 120 tons. Costs calculated in meters include material costs, work wages and heavy equipment used. The cost used in the 32x32x32 triangular minipile is 10% cheaper than the 28x28x28 m dimension.